Função social da propriedade fundiária: a (contra)proposta do movimento dos trabalhadores rurais sem-terra e os direitos fundamentais - Elias, Debora Nitz Ferreira (2009)
The present research aims to undertake a legal discussion about the effectiveness of the social function of land ownership in the face of the socialized conception of property proposed by the rural social movements, in MST, as a means of carrying out in the rural environment the stipulated fundamental rights in the Federal Constitution. It is certainly not an easy task, nor is it intended to exhaust the proposed theme, but it is hoped to contribute to a better understanding of the institutes that will be analyzed.